FAKTOR-FAKTOR YANG MELATARBELAKANGI IBU DALAM PEMBERIAN SUSU FORMULA PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS ROWOSARI KECAMATAN TEMBALANG SEMARANG TAHUN 2014 - Kunarsih Fitriana; Dina Rahayuning Pangestuti; Sri Achadi Nugraheni (Jurnal Kesehatan Masyarakat (Undip), 2015)
IDHS data 2012 showed that 31,5% baby aged 0-6 months and 18% baby age 2-3 months who continuing or breastfeeding dan other milk whereas BHR 2013 giving formula milk to baby age 0-6 months as much 90%. The porpuse this research is describe in depth predisposing factors, enabling factors, and reinforcing factors mother giving formula milk to baby age 0-6 months di Puskesmas Rowosari Semarang with qualitative method. Key informants in this research are 4 mother who have baby age 0-6 months giving formula milk with purpose sampling. Triangulasi infromants are 2 husband, 2 grandmother, and 1 active midwife. The result, predisposing factors giving formula milk to baby age 0-6 months who background by mother’s knowledge is less about exclusive breastfeeding, mother activity, and mother’s ecperience is less to giving exclusive breastfeeding. Enabling factors, formula milk easy to buy of baby’s parents because the place for to buy formula milk near with home which price to can reach for baby’s parents. Reinforcing factors mother giving formula milk to baby age 0-6 months because mother have less supporting from husband and her family. This research is expected to increase counselor personal exclusive breastfeeding and public is expected to follow caring saling of formula milk in places which to easy reach and have explicit attitude to baby’s parents to give exclusive breastfeeding.